Oral Ibrexafungerp: an investigational agent for the treatment of vulvovaginal candidiasis. (1st September 2020) - Azie, Nkechi; Angulo, David; Dehn, Barbara; Sobel, Jack D.
ABSTRACT: Introduction: Vulvovaginal candidiasis (VVC) is a common fungal infection caused by predominantly Candida albicans, and is diagnosed in up to 40% of women with vaginal complaints in the primary care setting. Approximately 75% of women experience at least one episode during their reproductive years. Areas covered: Ibrexafungerp is an orally active, semi-synthetic triterpenoid glucan synthase inhibitor under development for treatment and prevention of VVC. We present the chemistry, mechanism of action, pharmacology, microbiology, and results from clinical studies with ibrexafungerp in women with VVC. Expert opinion: Ibrexafungerp addresses several unmet needs with existing antifungal drugs as a first in a new class of antifungal agents with a novel mechanism of action demonstrating no antifungal cross resistance with azoles, and fungicidal activity against Candida spp., including fluconazole-resistant species. Some of the key attributes of ibrexafungerp related to VVC include oral one-day dosing, high tissue penetration, enhanced activity at low pH seen in the vagina, low risk for clinically significant drug–drug interactions, and a low risk of adverse events. If approved, ibrexafungerp will be the first new antifungal agent available for the treatment of VVC in more than 20 years and the only oral, non-azole antifungal approved for women suffering from VVC.